Radio Enhancing Innovative Technologies and Climate Information Service for Farmers in Ghana - Farm Radio, International, (2024)
This report provides an overview of activities completed in the second phase of the Radio Enhancing Innovative Technologies and Climate Information Service for Farmers in Ghana project. Building on the foundation laid in the first phase, the project continues to enhance farmers' access to climate-smart agricultural technologies and climate information services. Targeted to the Upper West, Upper East, Northern, Bono East, and Central regions, this phase re-engaged eight partner radio stations from the previous phase across the targeted regions. Activities carried out within July and October include stakeholder engagement, broadcaster training and content orientation, and program broadcast. A core technical workshop resulted in the development of a 16-week radio program tailored to meet the target audience's local needs, covering topics from stress-tolerant crop varieties to integrated pest management strategies. Each station delivered broadcasts in the local language, promoting gender-responsive agronomic practices, providing daily and weekly weather updates, and enhancing farmers’ knowledge of sustainable farming practices. All radio teams started broadcasting after training and content orientation. All stations with audio files submitted have aired a total of 64 live programs. The impact of these activities has been strengthened by engaging the Ghana Meteorological Agency, the Department of Agriculture, and other local partners, ensuring the relevance and practicality of the content. Regular program monitoring, field visits, and feedback loops are in place to refine the broadcasts further.